The Promotion of Physical Education since Preschool for the Comprehensive Development of Children (Innovaciones Educativas, 2024)
The essay addresses the importance of physical education in preschool and emphasizes the role it plays in the integral development of young children. It discusses Law 7800 and the mandatory nature of physical education in Costa Rica and the requirement to have specialized teachers to teach this subject.  It also discusses the benefits of physical education in childhood, which include the development of motor, cognitive and social skills, and urges more attention to this area in order to promote healthy habits from an early age, starting in preschool. It also highlights the long-term negative health effects that lack of physical activity can have on children and recommends that the infrastructure be appropriate for preschool age. It also stresses the importance of teachers being properly qualified to promote optimal child development, as this period is crucial for motor, cognitive, social and emotional development. The paper concludes that preschool physical education is important for the holistic development of children, promoting healthy habits and contributing to their well-being throughout their lives.
Keywords: Education; Physical Education; Preschool Education; Infancy; Childhood